Evaluation of the diagnostic value of different serum biomarkers in girls with central precocious puberty - Yasmine Abdelmeguid; Omneya Abdelkarem; Shaymaa Raafat (SpringerOpen, 2024)
Abstract Background Alarming trends show an increase in referrals of girls with suspected early puberty. However, variations in defining precocious puberty exist. GnRH stimulation test is the gold standard diagnostic test, which is expensive and challenging to interpret. Moreover, intravenous GnRH might not be available. Therefore, we sought to evaluate the diagnostic performance of basal serum Luteinizing Hormone and Anti-Mullerian hormone in girls with central precocious puberty, as an easier alternative to GnRH stimulation test. The study was conducted on 26 Egyptian girls presenting with early puberty at age < 8 years. Several evaluations including Tanner staging and GnRH stimulation test were performed. Basal serum luteinizing hormone, follicle stimulating hormone, and anti-Mullerian hormone were analyzed, and ROC curve was performed. Results The mean age of the patients at diagnosis was 5 ± 2.8 years. Most patients had breast Tanner 3 (76.9%). Bone age was advanced in 65.4% of patients. Basal luteinizing hormone level significantly differed between central precocious puberty and controls (p < 0.001), with an area under the curve of 0.840. A cut-off of 0.29 IU/L provided 84.62% sensitivity and 76.92% specificity. Conclusions Basal luteinizing hormone out-performs follicle-stimulating hormone and anti-Mullerian hormone as a screening tool and valuable indicator of central precocious puberty, potentially reducing the necessity of GnRH stimulation test.